2019
DOI: 10.1111/pbi.13037
|View full text |Cite
|
Sign up to set email alerts
|

NRT1.1B improves selenium concentrations in rice grains by facilitating selenomethinone translocation

Abstract: Summary Selenium (Se) is an essential trace element for humans and other animals, yet approximately one billion people worldwide suffer from Se deficiency. Rice is a staple food for over half of the world's population that is a major dietary source of Se. In paddy soils, rice roots mainly take up selenite. Se speciation analysis indicated that most of the selenite absorbed by rice is predominantly transformed into selenomethinone (SeMet) and retained in roots. However, the mechanism by which SeMet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 64 publications
0
52
1
2
Order By: Relevance
“…In contrast with the control Se-free rice which maintained a relatively stable expression of CAL1, its expression in the Se-rich rice decreased gradually to the lowest level in 40 μM of Se, indicating that CAL1 may negatively mediate the sensitiveness of Se application in the Se-rich rice. In addition, NRT1.1B, a member of the rice peptide transporter (PTR) family, is thought to improve the accumulation of Se in grains by facilitating selenomethinone (SeMet) translocation, provide novel insights into the breeding of Se-rich rice varieties [10]. In line with the previous report that roots of Se-hyper accumulator plants activate the expressions of ion transporters [49], the intervention on the expression activities of the abovementioned factors may contribute to the uptake capacity of Se for rice varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the control Se-free rice which maintained a relatively stable expression of CAL1, its expression in the Se-rich rice decreased gradually to the lowest level in 40 μM of Se, indicating that CAL1 may negatively mediate the sensitiveness of Se application in the Se-rich rice. In addition, NRT1.1B, a member of the rice peptide transporter (PTR) family, is thought to improve the accumulation of Se in grains by facilitating selenomethinone (SeMet) translocation, provide novel insights into the breeding of Se-rich rice varieties [10]. In line with the previous report that roots of Se-hyper accumulator plants activate the expressions of ion transporters [49], the intervention on the expression activities of the abovementioned factors may contribute to the uptake capacity of Se for rice varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Plant scientists believe that Se is a beneficial element, since it is involved in regulating plant growth and development, ranging from regulating plant photosynthesis and respiration, reducing free radicals damages, enhancing plant stress resistance, to alleviating the heavy metals-induced toxicity [1,6]. At the same time, it can increase the contents of chlorophyll and carotenoid leaves, reducing damages caused by ultraviolet-induced oxidative stresses [8][9][10]. It has been demonstrated that Se exhibits either beneficial or toxic effects on plant growth and development in a low or high concentration, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It means CAL1 may do not appear to affect selenium accumulation in rice roots. In addition, it was reported that NRT1.1B, a member of rice peptide transporter (PTR) family , holds great potential for the improvement of Se concentrations in grains by facilitating SeMet translocation, and the findings provide novel insight into the breeding of selenium-rich rice varieties [9]. Roots of Se-hyperaccumulator species have constitutively high expression of these genes, which might account for their large selenate uptake capacity [39].…”
Section: Discussionmentioning
confidence: 99%
“…For plants, some scientists believe that selenium is a beneficial element because it has many effects on plant growth and development, including regulating plant photosynthesis and respiration, reducing free radicals damage to plants, enhancing plant stress resistance, and alleviating the toxicity of heavy metals to plants [1,7]. At the same time, it can increase chlorophyll and carotenoid content in plant leaves, reduce damage caused by ultraviolet-induced oxidative stress [8], stimulate plant growth, and enhance plant tolerance or stress resistance to abiotic or biotic stresses [9]. Low selenium concentration is believed to be beneficial to plant growth and development, while high selenium concentration may be toxic to plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…По оценкам экспертов до миллиарда человек во всем мире страдают дефицитом селена [40]. Селенодефицит встречается крайне редко в странах Северной Америки, Японии и некоторых частях Южной Америки, тогда как в Европе, особенно Восточной, прослеживается умеренное потребление микроэлемента.…”
Section: Introductionunclassified